The Effect of Income and Social Status on Interests are not Smoking on Active Smokers - Mutia Arnisa Putri (Community Medicine and Education Journal, 2020)
Smoking is a phenomenon in society that emerged as an area of interest in research within the last decade, moreover due to the high prevalence in young adults. This research was conducted to determine factors that influenced interest in smoking consumption, including the aspects of income and social status toward the interests of active smokers in Palembang to quit their smoking behavior. The methods used was qualitative research and data were taken by observations, focus group discussion (FGD) and in-depth interview. The informants were 15 active smokers from various backgrounds in Palembang that were selected by purposive sampling technique. In FGD, out of 15 informants, 10 were taken and divided into 2 groups, and the rest 5 informants were chosen for in-depth interview. Based on the three aspects of planned behavior theory, i.e. individual’s interest, subjective social norm, and behavioral control, the result showed that individual’s attitude did not influence the decision of active smokers to quit their smoking behavior, meant as not to quit but more inclined to reduce than to stop. Second, based on subjective social norm, from environment, parents, and peers, the result showed that this aspect could influence active smokers’ interest to quit smoking. Third, based on the aspect of behavioral control by individual’s income, the result showed that the income did not influence active smokers’ interest to quit smoking because they were more driven by their cravings for cigarette. Based on behavioral control by social status, the results showed that educational level and marriage status did have influence on active smokers to their smoking behavior, but not to stop, rather only to reduce. The aspect of jobs also did not have any influence on active smokers to quit their smoking behavior.